2006
DOI: 10.1007/s10554-005-9064-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential interest of intra-aorta ultrasound imaging for the diagnosis of aortic penetrating atherosclerotic ulcer

Abstract: A 72-year-old man was admitted to our hospital for acute back pain. Transesophageal echocardiography (TEE), computed tomography (CT) and magnetic resonance imaging (MRI) all showed the presence of intramural hematoma (IMH) located in the descending aorta, with bilateral pleural effusions. The patient was initially referred for medical therapy and 'watchful waiting'. However, he continued to have back pain, so we decided to perform invasive aortography examination and intra-aortic ultrasound (IAU) imaging. No p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Weintraub et al [ 26 ] in 1990 is the first to use IVUS for the assessment of a patient with aortic dissection. Since then, there are several reports and studies described in the literature about the application of IVUS for imaging of the diseased aorta [ 27 29 ]. In 1985 Hughes et al [ 30 ] described an in vivo experiment to evaluate aortic distention in dogs by intravascular ultrasonic catheter with simultaneous measurement of intra-aortic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Weintraub et al [ 26 ] in 1990 is the first to use IVUS for the assessment of a patient with aortic dissection. Since then, there are several reports and studies described in the literature about the application of IVUS for imaging of the diseased aorta [ 27 29 ]. In 1985 Hughes et al [ 30 ] described an in vivo experiment to evaluate aortic distention in dogs by intravascular ultrasonic catheter with simultaneous measurement of intra-aortic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly useful in assessing the presence of IMH or PAU if other methods give inadequate results, but as an invasive procedure and due to its limited availability, it is not a first step modality in AD diagnosis [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound, with its sensitivity and specificity close to 100% in evaluating AD, overcomes known limitations of conventional aortography as the aortic wall is visualized from inside the lumen. It is particularly useful in assessing the presence of IMH or PAU if other methods give inadequate results, but as an invasive procedure and due to its limited availability, it is not a first step modality in AD diagnosis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that progression of the PAU was slow, with a low prevalence of acute rupture or other life-threatening complications (21). Other authors reported a more negative prognosis with respect to classic aortic dissection, with a high incidence of complications (3,4,10,11,(15)(16)(17)22).…”
Section: Natural Evolutionmentioning
confidence: 99%
“…TEE has been less well studied than CT and MRI for the diagnosis of PAU of the aorta, so its utility as a diagnostic tool for this condition is unknown (17). Only some published case reports suggest that TEE can successfully identify this pathology (22). TEE offers some advantages that include portability and the ability to obtain high-resolution images of the aortic wall (17).…”
Section: Diagnosismentioning
confidence: 99%